Comparison of Rodent Vector Control Methods: a Scoping Review - Najoan, Graciela Carina; Namira, Nurhayati (BKM Public Health and Community Medicine, 2024)
Purpose: This research aims to identify, categorize, and evaluate the effectiveness, efficiency, and environmental impact of various methods used to control rodent vectors in different studies. Method: This research uses a scoping review method with a search of the PubMed database for free full-text articles using the keyword "rodent vector control." Out of 3366 research journals found, only 9 met the inclusion criteria. Information was collected from these 9 journals regarding the control methods used, their effectiveness and efficiency, as well as the reported environmental and public health impacts over the publication range of 2014-2024. Data analysis was conducted qualitatively by presenting and compiling the research report. Results: Each rodent vector control method has its advantages and disadvantages. Physical methods such as rat traps are cost-efficient and have minimal contamination with hazardous substances for the environment, but they are less effective for killing large numbers of rats. Chemical methods like rodenticides are highly effective in reducing rat populations, but they can be toxic to human health and cause long-term environmental contamination. Biological methods such as natural predators and pets are more environmentally friendly but require time to achieve effectiveness. Ultimately, the most appropriate rodent vector control method must be chosen based on specific needs and situations and should be integrated. Conclusion: Rodent vector control requires an integrated approach, including biological, chemical, and physical methods, while considering their long-term impact on public health and the environment. The implementation of biological methods needs to consider ecosystem balance, while the use of chemicals must be cautious to avoid harmful side effects on environmental and public health. Integrating physical approaches should also be applied to reduce rodent habitats without damaging the surrounding environment. Effective and safe rodent vector control can be achieved, supporting sustainable public health.